Meshugah - Singer, Isaac Bashevis 1902-1991 (Farrar, Straus, Giroux, 1994)
A romantic triangle involving survivors of the Holocaust, set in New York City in the 50s. It was serialized in the Yiddish newspaper, Forward, under the title Lost Souls.